A technique for the production of bacteria-free planting stock of cassava (Manihot esculenta Crantz) - Lozano, J.C.; Wholey, W (International Center for Tropical Agriculture, 1973)
A method of rooting shoot tips is described, whereby plants free from cassava bacterial blight were produced. The use of this method, in addition to cultural practices, is proposed for producing pathogen-free foundation stock for a planting material certification program. (AS)